Religiosity and Righteousness: A Critique of Islamic and Christian Practices on the University of Ibadan Campus - Oladosu, Uthman Habibat (IJUS | International Journal of Umranic Studies, 2023)
As it is in the larger Nigerian society, the University of Ibadan campus is replete with religious groups and associations with affiliation to Islam and Christianity. Contrary to the fundamental dictates of these two religions however, the history of relationship between the Muslim and Christian communities on campus has been circumscribed, in the main, by suspicion, hatred and, sometimes, outright conflict. The gulf between religious texts and practices on Ibadan campus is equally manifest among Christian and Muslim students some of whom have been found guilty of examination malpractices, cultism and illicit sexual relations among other acts that both Islam and Christianity have designated as acts of unrighteousness. This paper, therefore, sets out to achieve the following: a) interrogate the concept of righteousness in both Islam and Christianity and, b) situate the latter against the general notion of religiosity on Ibadan campus. The paper relies heavily on the assumption that religious activism should be an instrument of character building and a catalyst for peaceful coexistence. The paper uses the descriptive method in eliciting data and sources its theoretical discussion from existing literature on the subject. The paper finds the following questions very important: exactly how does religiosity on the University of Ibadan campus translate to righteousness? How do we account for intra/inter-religious conflicts that often occur on the campus despite the outward display of religious identities by all? In other words, how far has the manifestation of religious identities by Muslims and Christians on the Ibadan campus been useful for the enhancement of godliness? This paper concludes that both Islam and Christianity, when properly understood and their tenets carefully applied, have models that can guarantee the establishment of righteous and godly society for the Nigerian nation at large.